Capital Markets in Southeast Europe Origins and Efficiency in a Cross-Country Analysis of Transition Economies - Dodig, Ante. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
"The capital markets industry is at the forefront of financial innovation and it is a determining element in the wider socio-economic ongoings. The author effectively contrasts cross-industries associating theories with empirical statistical findings ascribing certainty to the capital markets structure and role inefficiencies while endorsing opportunities for improvements for the inclusive outlook. Through international perspective the writing demonstrates how globalization trend, or its reversal, dichotomously impact productivity and growth and meaningfully so by an increasing contribution from developing economies." -Kudret Akgun, Chief Investment Officer and Global Head of Debt Capital Markets and Housing Finance at International Finance Corporation, Washington, D.C. "The work by Ante Dodig is built upon juxtaposing complementary pillars. On one side the story reflects the development and profiling through the first three decades from nascence of capital markets in southeast Europe. On the other side the book provides extensive empirical evidence in statistical significance for capital markets inefficiency in its weak form. The narrative dispels frequent transitioning markets' inconclusiveness and inconsistencies through constituting a factual analysis of capital market role and innovation in economic output. As the author recalls, it is the surrounding environment that shapes and determines operations as one result is not hereditary to another." -George M. Jabbour, Vice Dean for Executive Education, Program Director for Master of Science in Finance, and Professor of Finance, School of Business, The George Washington University, Washington, D.C. Ante Dodig is an Investment Officer at International Finance Corporation with over a decade of global experience in developing markets through leading groundbreaking institutional financial investing in emerging economies. He has a Master's of Science in Finance and a PhD in Business Management while university teaching international courses on Investments, Investment Banking, and Capital Markets.
Chapter One: Introduction -- Chapter Two: Global and Southeast European Environment -- Chapter Three: Profiling Individual Capital Markets In The Selected Southeast European Countries -- Chapter Four: Research Statistical Approach Framework And Empirical Testing Results -- Chapter Five: Summary Closing Considerations And Recommendations.
Keywords: Capital market; Development economics; Economic development; Capital Markets; Development Economics; Economic Growth